2023
DOI: 10.3390/s23041988
|View full text |Cite
|
Sign up to set email alerts
|

Modal Decomposition of Acoustic Emissions from Pencil-Lead Breaks in an Isotropic Thin Plate

Abstract: Acoustic emission (AE) testing and Lamb wave inspection techniques have been widely used in non-destructive testing and structural health monitoring. For thin plates, the AEs arising from structural defect development (e.g., fatigue crack propagation) propagate as Lamb waves, and Lamb wave modes can be used to provide important information about the growth and localisation of defects. However, few sensors can be used to achieve the in situ wavenumber–frequency modal decomposition of AEs. This study explores th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Yao et al [ 6 ] investigated the capabilities of a commercial AE (Acoustic Emission) sensor in decomposing AE wave modes generated by pencil lead breaks (PLBs) on a thin metal plate incorporating the LAMDA (linear array for modal decomposition and analysis) sensor and finite element analysis (FEA). It is shown that a transverse PLB produces a dominant A0 mode, while a longitudinal PLB produces a combination of A0 and S0 modes.…”
mentioning
confidence: 99%
“…Yao et al [ 6 ] investigated the capabilities of a commercial AE (Acoustic Emission) sensor in decomposing AE wave modes generated by pencil lead breaks (PLBs) on a thin metal plate incorporating the LAMDA (linear array for modal decomposition and analysis) sensor and finite element analysis (FEA). It is shown that a transverse PLB produces a dominant A0 mode, while a longitudinal PLB produces a combination of A0 and S0 modes.…”
mentioning
confidence: 99%